PENGARUH PENGEMBANGAN KARIR DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KEMENTERIAN KELAUTAN DAN PERIKANAN - Aflah Alfi Syania; Hasanah Hasanah (Taksasila Edukasi Insani, 2026)
This study aims to analyze the effect of career development and work discipline on employee performance at the Ministry of Marine Affairs and Fisheries, Directorate General of Marine Spatial Management. This research employs a quantitative approach with a causal associative method. The population consists of all employees, with 46 respondents selected using a saturated sampling technique. Data were collected through Likert-scale questionnaires and analyzed using multiple linear regression. The results indicate that career development and work discipline have a positive and significant effect on employee performance, both partially and simultaneously. These findings highlight the importance of strengthening merit-based career development systems and consistent work discipline to improve civil servant performance.Keywords : Career development, work discipline, employee performance